Penggunaan Model Pembelajaran Numbered Heads Together dengan Permainan Kalimat Berantai dalam Meningkatkan Keterampilan Menulis Teks Fiksi - Rosdiyatul Munawaroh; Iis Ristiani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This study discusses the low interest of students in learning to write fiction texts in influencing the final score to be the background of the research. The purpose of this study is to explore the effectiveness of using the Numbered Heads Together (NHT) learning model with chain sentence games in fictional text writing skills in grade V students of SDN Bangbayang 2. This research method uses a quasi-experimental design for the control group and the experimental group with a total of 15 students in each group. The results showed that the average score of the assessment aspects which included themes, characters, plot, background and language style experienced a significant increase from the experimental group with posttest results (80.00, 89.00, 80.00, 81.33, 88.33) greater than the average score of the pretest (64.33, 71.67, 62.33, 69.67, 74.00). In the control group, the average score obtained during the posttest (77.00, 72.67, 68.67, 74.00 73.67) was also greater than the average score of the pretest (74.00, 70.00, 60.00, 70.33, 69.33), but not as large as the increase obtained by the experimental group. In five aspects of assessment, the analysis of the t-test showed significant t-values (12.67, 14.66, 9.00, 7.99 and 9.99). The conclusion of this study is that the Numbered Heads Together learning model with chain sentence games is effective in improving fiction text writing skills in grade V elementary school students.